Ранняя социалистическая модель государства и общества. Утопия Павла Пестеля в 1820-х гг. - Бебеши, Дьёдь; Колонтари, Аттила (SlavVaria, 2024)
An Early Socialist Model of State and Society. Pavel Pestel's Utopia in the 1820s. Pavel Pestel was an outstanding member of Decembrist movement, a leader of its radical wing, the Southern Society. The article offered to the readers' attention studies his main work, Russkaya Pravda (Russian Truth), where he outlined his concept of radical reorganisation of the Russian state. In addition, Pestel, as a convinced supporter of the republic, pays great attention to the future state system, describes in detail the organs of government, their subordination and powers. His system of views was a peculiar mixture of European liberal thinking and Russian imperial traditions. The means he proposed – violent seizure of power, liquidation of the imperial family, introduction of dictatorship and censorship, total surveillance of society – make him an early predecessor of the Bolsheviks.